Static gait planning method for quadruped robots on uneven terrain. (29th January 2022) - Wang, Qixin; Ke, Wende; Wen, Qi; Li, Huazhong; Zhang, Jian
In order to improve the stable walking ability of quadruped robot in uneven terrain, the discontinuous gait of quadruped robot is designed based on the stability margin calculated by the pressure center method. Gait planning includes body centre of gravity trajectory planning and swing foot end trajectory planning. Sine acceleration curve is used to plan the body centre of gravity trajectory to ensure the continuity of the whole movement process. Aiming at the robot with the ability of environment perception, a kind of rectangular swinging foot end trajectory is designed, which has both flexible adaptability and moving speed. The simulation results show that the quadruped robot can pass through the uneven terrain area in real time and stably using the proposed static gait planning method.